2013
DOI: 10.1111/rda.12180
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Development of Bison Embryos Using Interspecies Somatic Cell Nuclear Transfer

Abstract: Interspecies somatic cell nuclear transfer (interspecies SCNT) has been explored in many domestic and non-domestic animal species. However, problems arise during the development of these embryos, which may be related to species-specific differences in nuclear-cytoplasmic communication. The objectives of this study were to investigate the possibility of producing bison embryos in vitro using interspecies SCNT and assess the developmental potential of these embryos. Treatment groups consisted of cattle in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The rates of SCNT blastocyst formation in bovine and mouse were more than 25% and were comparatively determined as higher efficiency than those of porcine SCNT (10%–17%) during in vitro pre‐implantation period. Furthermore, total cell number of porcine SCNT blastocysts consisted of 26–50 cells was generally lower than values from bovine or mouse SCNT blastocysts, which was more than 100 cells or approximately 60 cells, respectively (Chen et al., ; Costa‐Borges et al., ; Kumar et al., , ; Lee et al., ; Pan et al., ; Seaby et al., ). But in the present study, even after supplementing with autologous ooplasm into SCNT (AOT) embryos, no significant increases in the values of cleavage rate, blastocyst formation, hatched blastocyst and total cell number in comparison with SCNT embryos were observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rates of SCNT blastocyst formation in bovine and mouse were more than 25% and were comparatively determined as higher efficiency than those of porcine SCNT (10%–17%) during in vitro pre‐implantation period. Furthermore, total cell number of porcine SCNT blastocysts consisted of 26–50 cells was generally lower than values from bovine or mouse SCNT blastocysts, which was more than 100 cells or approximately 60 cells, respectively (Chen et al., ; Costa‐Borges et al., ; Kumar et al., , ; Lee et al., ; Pan et al., ; Seaby et al., ). But in the present study, even after supplementing with autologous ooplasm into SCNT (AOT) embryos, no significant increases in the values of cleavage rate, blastocyst formation, hatched blastocyst and total cell number in comparison with SCNT embryos were observed.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally addressed that the ratio of blastocyst formation in SCNT embryo during in vitro pre-implantation development is approximately 25%-33% in mouse and bovine, whereas that of porcine has still remained below 20% (Costa-Borges, Gonzalez, Santaló, & Ibáñez, 2011;Kumar et al, 2007;Lee et al, 2014;Pan et al, 2015;Seaby, Alexander, King, & Mastromonaco, 2013;Xu et al, 2013). As there have been considerable achievements of the application of OT, it can be possibly applied to porcine SCNT research to overcome low efficiency of embryo development.…”
Section: Introductionmentioning
confidence: 99%
“…iSCNT studies have demonstrated the ability of enucleated oocytes to support first mitotic division with subsequent failure to activate embryonic genes [ 12 , 13 ]. In wild cattle iSCNT embryos, evidence of increased developmental arrest compared to SCNT controls was observed at the 8–16 cell stage (gaur: [ 14 ]; bison: [ 15 ]). Therefore, supplementing ooplasm from the same species as the somatic cell into iSCNT embryos could influence embryo development by transferring species-specific proteins, organelles, and other molecules [ 8 , 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous iSCNT experiments conducted in our laboratory used somatic cell donors from two North American bison subspecies ( Bison bison bison and Bison bison athabascae ) and domestic cattle oocytes to investigate potential causes responsible for embryonic arrest commonly observed at the 8–16 cell stage [ 15 , 19 ]. Numerous analyses performed at this stage of development showed alterations in mitochondrial function (metabolism, apoptosis, transcription) predominantly in bison iSCNT embryos [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…After the transfer of nuclei from sheep, pig, monkey or rat skin cells to MII enucleated cattle oocyte the cytoplast and xenogenic karyoplast joined. In further experiments cattle oocytes were used as cytoplasts in transfer of somatic cell nuclei of pigs (71), koala (72), antelope, goat (73), horses (74), black bear (75), mountain antelope (76), hens (77), yak and dog (78), and buffalo (79). These cytoplasts are preferable because of their low cost (due to isolation from ovaries of slaughtered animals) and easy cultivation which allows 90 % maturation.…”
Section: First Cloned Progeny In Different Animal Speciesmentioning
confidence: 99%